P07.22 Performance characteristics of an automated assay on the cobas® 4800 system to detect herpes simplex virus from genital lesion specimens with the cobas® hsv 1 and 2 test. (13th September 2015) - Chio, M; Aminah, S; Osiecki, J; Lewinski, M; Low, L
Abstract : Introduction: Herpes simplex viruses occur worldwide and laboratory confirmation is recommended using methods that directly demonstrate presence of the virus in genital specimens. This study was conducted to establish performance characteristics for the cobas® HSV 1 and 2 Test by evaluating genital lesion samples compared to standard of care viral isolation. Methods: This evaluation study was conducted using 193 clinical swab specimens from active lesions of suspected herpes simplex collected at the DSC Clinic during the period of April 2014 through October 2014. The results of the cobas® HSV 1 and 2 Test were compared with those obtained from viral isolation. Samples with discordant results for HSV-1 and HSV-2 were confirmed with an in-house HSV PCR performed at Singapore General Hospital. Results: Of the 193 samples tested for HSV-1, 27 were positive and 159 were negative with both the cobas® HSV 1 and 2 Test and viral isolation. Of the samples evaluated, 7 were positive by the cobas® HSV 1 and 2 Test but not in viral isolation. The overall agreement of the cobas® HSV 1 and 2 Test and viral isolation for HSV-1 was 96.4%. Of the 193 samples tested for HSV-2, 57 were positive and 113 were negative with both the cobas® HSV 1 and 2 Test and viral isolation. There were 23 samples found to be positive with the cobas® HSV 1 and 2 Test but not in viral isolation. The overall agreement of the cobas® HSV 1 and 2 Test and viral isolation for HSV-2 was 88.1%. Further testing of discrepant samples revealed 20/23 were detected by an in-house HSV PCR assay. Conclusion: The cobas® HSV 1 and 2 Test, run on the fully automated cobas® 4800 system, demonstrated excellent performance for detecting HSV 1 and 2 from clinical specimens when compared with viral isolation. Disclosure of interest statement: The Department of Sexually Transmitted Infections Control Clinic, Singapore collaborated with Roche Molecular Systems on the presentation of the outcomes of this evaluation study.